Photochemistry of 1-phenyl-1-diazopropane and its diazirine isomer: A CASSCF and MS-CASPT2 study - Soto-Martín, Juan (ACS, 2022)
In this work, we studied the wavelength (520 or 350 nm) dependence of the photochemical decomposition of 1-phenyl-1-diazopropane (PDP) and 1-phenyl-1-propyl diazirine (PED) by means of high-level ab initio quantum chemical calculations (CASSCF and MS-CASPT2) to obtain qualitative and quantitative results. It is found that the photochemistry of PDP is governed by nonradiative deactivation processes that can involve one or two S1/S0 conical intersections (CI1 and CI2) depending on the wavelength of the radiation; CI2 is only accessible at the shortest wavelength. It is demonstrated that the main intermediate of the photochemistry of the titled compounds is 1-ethyl-1-phenyl carbene (EPC). Upon irradiation of PDP with the 520 nm light, the carbene is always generated in its ground state as closed-shell singlet carbene. In contrast, the 350 nm radiation can directly decompose PDP into S1 carbene (open shell) and N2 when the conical intersection CI2 is avoided. Once the carbene is formed in the S1 state, it can experience excited state intramolecular proton transfer along a seam of crossing (ESIPT-SC) of the S1 and S0 states to yield the alkene derivative; that is, the proton transfer reaction takes places on a degenerate potential energy surface where the two electronic states have equal energy. In addition, it is found that EPC absorbs at 350 nm (double excitations); therefore, there is another possible route that can induce as well a slightly different photochemistry in changing the wavelength of the radiation because the shortest wavelength (when it is intense enough) decreases the amount of available EPC or generates a highly vibrationally excited state of the carbene; that is, after 350 nm excitation, the carbene intermediate can deactivate via radiation emission or can decay through a cascade of conical intersections to its first excited state (S1), where ESIPT-SC is operative again.
Keywords: Estructura molecular; Carbono -- Compuestos; Carbene compounds; Excited states; Molecular structure; Transition states; Quantum mechanics